Safe intra-hospital care in context of vulnerability to socio-environmental disasters: implications for nursing - Mayra Wilbert Rocha; Alexandre Barbosa de Oliveira; Diego Freitas de Araújo; Ana Beatriz Azevedo Queiroz; Graciele Oroski Paes (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objectives: to analyze the factors involved in safe intra-hospital care, in a context of vulnerability to socio-environmental disasters and their implications for nursing. Methods: a cross-sectional study of a descriptive and exploratory nature. Semi-structured interviews were conducted with 49 nursing professionals from a hospital in the mountainous region of the state of Rio de Janeiro (Brazil), which suffered a significant impact from a socio-environmental disaster in January 2011. Data were processed by software IRaMuTeQ. Results: aspects related to disaster assistance were presented through a thematic chunk with four classes, through descending hierarchical classification. Conclusions: for better nursing response in socio-environmental disasters, in an intra-hospital setting, investments for training and continuing education should be prioritized; adequate provision and provision of human, material and technological resources; psychological support for professionals after such events; appropriation of nursing competencies for the development of advanced practices in disasters and effective risk management.